Penyuluhan Gizi Seimbang dan Pemeriksaan Status Gizi dengan MNA-SF pada Lanjut Usia - Purwantini, Dwi; Rassa, Alida Nella Fedelina; Setyawati, Emiliana Indah Eko (Jurnal Abdimas Kesehatan (JAK), 2025)
Life expectancy of Indonesian elderly has increased recently due to the success of development in various fields, especially Health. Most elderly people has experiencing or at risk of malnutrition. Malnutrition is characterized by weight loss including loss of skeletal muscle mass and has a negative impact on muscle strength. This Community Service aim is to increase the knowledge of the elderly about balanced nutrition. Health Education is carried out through counseling, Q&A, and demonstration media. The results of the nutritional status examination were most of the elderly group of Corps 4 Surabaya, namely 18 elderly (89%) have normal nutritional status, 2 elderly (11%) are at risk of malnutrition. After providing the material, most of the elderly (94%) understand what is being conveyed. The use of appropriate health education media is expected to increase the target of education knowledge, especially malnutrition. This education is ultimately expected to change a positive behaviour Health. Normal nutritional status can reduce mortality rates, reduce chronic diseases, increase mental and cognitive abilities, depression conditions, psychological health, independence, balance of bone and muscle strength and quality of life in the elderly.